Analysis of Students Mathematical Reasoning in Solving Cuboid and Cube Problems Based on Learning Styles. - Ayu Wanlin, Agnes Putri; Parta, I Nengah; Rahardjo, Swasono (PRISMA, 2025)
Mathematical reasoning ability is an important skill that students must have in the process of learning mathematics. This skill allows students to develop logical, analytical, systematic, critical, and creative thinking patterns. Based on this, the researcher examined the mathematical reasoning ability of grade VII students at SMP Negeri 2 Pakisaji in solving story problems about blocks and cubes. This study is entitled "Analysis of Students' Mathematical Reasoning Ability in Solving Cuboid and Cube Story Problems Reviewed from Learning Styles" and uses a descriptive qualitative approach. This study involved 30 students, of which 6 students would be selected for analysis, with 2 students from each category of high and low learning styles. Data collection methods include learning style tests, written tests, interview guidelines, and documentation. The results of the study showed that students with visual learning styles and high mathematical reasoning abilities can present, ask questions, make guesses, perform mathematical manipulations, draw conclusions, and check the correctness of answers. In contrast, students with low mathematical reasoning abilities have not been able to do these things. The same thing is also seen in students with auditory and kinesthetic learning styles who have high mathematical reasoning abilities, where they can do similar activities, while students with low mathematical reasoning abilities still face difficulties.